2016
DOI: 10.3390/soc6030019
|View full text |Cite
|
Sign up to set email alerts
|

Special Education Teacher Leadership in Jordan: Current State and Constraints

Abstract: Distributed leadership can enhance the professional learning communities of schools. The present study explored the leadership experience of Jordanian special education teachers, and their perceptions of common constraints to leadership. A mixed method design was used, including a survey (n = 136) and an interview (n = 23). Results indicated that special education teachers had little experience of leadership roles. They regarded the provision of cognitive and emotional support to colleagues as their most impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The results showed that special education teachers have a low level of leadership. This result agrees with the findings of previous studies, which found and confirmed that the perceived leadership roles of special education teachers were limited in scope and frequency [14]. The results of this study disagree with the results of a previous study, which stated that special education teachers play leadership roles at high levels, and the perception of special education teachers regarding the practice of classroom management has been positively correlated with the practice of teacher leadership [13].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The results showed that special education teachers have a low level of leadership. This result agrees with the findings of previous studies, which found and confirmed that the perceived leadership roles of special education teachers were limited in scope and frequency [14]. The results of this study disagree with the results of a previous study, which stated that special education teachers play leadership roles at high levels, and the perception of special education teachers regarding the practice of classroom management has been positively correlated with the practice of teacher leadership [13].…”
Section: Discussionsupporting
confidence: 73%
“…There is a consensus in the literature that leadership among general education teachers and the leadership roles of special education teachers are rarely mentioned [14]. This gap is particularly important, not only because the restructuring of education changes the tasks and behaviour of workers in education, but also changes the management of professional relationships.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the great attention to teacher leadership in Western countries, there is a dearth in studies related to teacher leadership in Arab countries (Al-Taneiji & Ibrahim, 2017;Al-Zboon, 2016;Ramahi & Eltemamy, 2014). This lack of research becomes ever more necessary as several Arab countries have launched educational reforms in their countries in order to improve their educational systems (Alfadala, 2015;El-Baz, 2009;Karami-Akkary, 2014).…”
Section: Introductionmentioning
confidence: 99%